I only know how to simplify Taboolian Expressions!
So I'm assuming v is OR (union) and the brackets of course are AND (product). In which case, (x V y)(x' V y) = (x x') V (x y) V (x' y) V (y y) = 0 V xy V x'y V y = (xVx')y V y = yOr rather just (x V y)(x' V y) = (xx')Vy = yIs it?
That is exactly the answer I got the first time I did it. It didn't look right though, so I left the answer till the third step.Thanks anyway for the effort.
Nice blog, please take a look at mine and link it up here.Thanks
hey Ahmed, didn't you leave a comment about your blog a year ago?Alright, no more advertising comments from now on.